Jaga Harapan as an Integrated Economic Empowerment Program of Laznas Salam Setara - Ary Maulana; Ety Rahayu; Siti Rodiyah (International Journal of Science and Society, 2026)
Empowerment is a process aimed at increasing the capacity and power of disadvantaged groups. Salam Setara Amil Zakat Institution has developed an integrated empowerment initiative called Jaga Harapan under the broader Zakat Plus program. Jaga Harapan is an integrated program that provides business capital assistance, entrepreneurship training, spiritual development, and social character building. The program aims to support business growth, improve the quality and consistency of religious practices, and foster stronger social character among beneficiaries. This study seeks to describe the empowerment efforts implemented through the Jaga Harapan program, which is distinctive due to its beneficiaries being spread across various regions of Indonesia and the program activities being conducted entirely online. This research employs a qualitative descriptive approach to analyze the implementation of the Jaga Harapan program using the concepts of empowerment, training, and mentoring.